Hubungan Tingkat Pengetahuan Terhadap Perilaku Swamedikasi Demam Di Desa Bumi Dipasena Abadi Lampung - Hasna Fadlu Rahma; Sakti Pambudi, Risma; Qonitah, Fadilah (Melekliterasi Press, 2025)
Self-medication is one of the most general treatments for minor illnesses such as fever. Self-medication in Indonesian society is quite high, but health workers do not provide complete information about the correct use of drugs. The study aims to determine the correlation between the level of knowledge and self-medication behavior for fever at Bumi Dipasena Abadi Village in Lampung. The research is an analytical correlational study using a cross-sectional approach. The sample amounted to 100 respondents. The research instrument used a questionnaire that had passed the validity and reliability test. The results show that the level of knowledge about fever is high at 91%, moderate at 8%, and 1% is categorized as the low category. Self-medication behavior is categorized as 96% in the good category, 3% in the sufficient category, and 1% in the poor category. Data analysis implemented univariate and bivariate analysis using the chi-square test and obtained a p-value of 0.002 (P<0.05). It shows that there is a significant correlation between the level of knowledge and self-medication behavior for fever.